Nitrofurantoin Combined With Amikacin: A Promising Alternative Strategy for Combating MDR Uropathogenic Escherichia coli - Zhong, Zi-Xing; Cui, Ze-Hua; Li, Xiao-Jie; Tang, Tian; Zheng, Zi-Jian; Ni, Wei-Na; Fang, Liang-Xing; Zhou, Yu-Feng; Yu, Yang; Liu, Ya-Hong; Liao, Xiao-Ping; Sun, Jian (Frontiers in Cellular and Infection Microbiology, 2020)
Urinary tract infections (UTI) are common infections that can be mild to life threatening. However, increased bacterial resistance and poor patient compliance rates have limited the effectiveness of conventional antibiotic therapies. Here, we investigated the relationship between nitrofurantoin and amikacin against 12 clinical MDR uropathogenic Escherichia coli (UPEC) strains both in vitro and in an experimental G. mellonella model. In vitro synergistic effects were observed in all 12 test strains by standard checkerboard and time-kill assays. Importantly, amikacin or nitrofurantoin at half of the clinical doses were not effective in the treatment of UPEC infections in the G. mellonella model but the combination therapy significantly increased G. mellonella survival from infections caused by all 12 study UPEC strains. Taken together, these results demonstrated synergy effects between nitrofurantoin and amikacin against MDR UPEC.